The Influence of Strengthening Islamic Religious Education through a Religious Culture on Students' Religious Behavior at Private Junior High School Harapan 3 Medan - Fathinatul Wafiqah Lubis; Asnil Aidah Ritonga; Yusnaili Budianti (EDUJAVARE: International Journal of Educational Research, 2026)
Addressing the gap between cognitive understanding and practice in Islamic Education (PAI) caused by theoretical-rote methods, this study analyzes the impact of PAI reinforcement based on religious culture on student behavior at SMP Swasta Harapan 3 Medan. Using a quantitative associative method with simple random sampling on 100 eighth-grade students and linear regression analysis, the results indicate that, while both PAI reinforcement and student religious behavior are currently in the moderate category, there is a positive and significant influence with a 43.6% contribution (R Square) and a regression model of Y = 63.596 + 0.572X. The study concludes that engineering the school ecosystem based on behavioristic theory is effective for shaping daily Islamic character, recommending further research into external factors like family and community, as 56.4% of the variance lies outside this model.